О НОВЫХ НАХОЖДЕНИЯХ МОРСКОГО СУДАКА SANDER MARINUS В СЕВЕРО-ВОСТОЧНОЙ ЧАСТИ КАСПИЙСКОГО МОРЯ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
New records of the Estuarine Perch Sander marinus (Cuvier, 1828) (Perciformes) are given, from the north-eastern part of the Caspian Sea (Kazakhstan waters).